MASALAH SOSIAL MASYARAKAT JEPANG PASCA PERANG DUNIA II DALAM NOVEL SAGA NO GABAI BAACHAN KARYA YOSHICHI SHIMADA - Trisna Surmadewi, Ida Ayu (Humanis, 2014)
Normal 0 false false false EN-US X-NONE X-NONE MicrosoftInternetExplorer4 This thesis entitled “ social problem of Japan after World War II in the novel Saga no Gabai Baachan by Shimada Yoshichi” . Sources of data used in this study is novel Saga no Gabai Baachan. Analysis of social problems using the theory of social problems Soerjono Soekanto and author worldview analysis using genetic structuralism theory of Faruk.The results of the analysis indicate a variety of social problems experienced by the people of Japan after World War II. While the analysis is the author's view of the world view of yoshichi Shimada understanding of the various social problems that occurred in Japan. /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-qformat:yes; mso-style-parent:""; mso-padding-alt:0cm 5.4pt 0cm 5.4pt; mso-para-margin-top:0cm; mso-para-margin-right:0cm; mso-para-margin-bottom:10.0pt; mso-para-margin-left:0cm; line-height:115%; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:"Times New Roman"; mso-fareast-theme-font:minor-fareast; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:"Times New Roman"; mso-bidi-theme-font:minor-bidi;}
Keywords: Social problems, worldview author